General Practice Patients' Readiness to be Treated With Brief Intervention to Reduce Alcohol Consumption: A Cross-Sectional Study With Between-Subject Design. (22nd October 2020) - Fankhaenel, Thomas; Mueller, Anna-Maria; Frese, Thomas
Abstract: Aims: To treat excessive alcohol consumption, general practices (GPs) are recommended to use non-directive implementation strategies. Directive implementation, however, may be perceived by general practice patients as something positive because of possibly indicating higher GP engagement and a more consistent treatment. In our study, we aimed to assess the readiness of patients to be treated with BI in the hypothetical event of excessive alcohol consumption either by a GP using non-directive recommendations according to WHO or by a GP using directive instructions. Additionally, we assessed the patients' dispositional readiness to disclose alcohol-associated personal information, termed alcohol consumption self-disclosure, in order to analyze its influence on their readiness to be treated with brief intervention (BI). Methods: When consulting their GP, a convenience sample of general practice patients was asked by questionnaire. By means of a between-subject design, they were asked for the readiness to be treated either with non-directive BI or with directive BI. Repeated-measure ANCOVA was used to analyze the main- and interaction effects. Results: A sample of 442 general practice patients preferred the non-directive BI, F (1, 423) = 5.56, P < 0.05. We found moreover a two-way interaction between implementation and alcohol consumption self-disclosure, F (1, 423) = 18.89, P < 0.001, showing that only patients with low self-disclosure preferred the non-directive BI, t (428) = 3.99, P < 0.001. Conclusions: Future research should investigate the reasons for the patients' preference for the non-directive BI and may develop strategies to overcome the possibly low readiness of general practice patients to be treated with BI.